Electrolytic copper graphene composite foil and method for preparing the same
Patent Information
- Application Number
- CN202611157933.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-31
- Publication Date
- 2026-10-09
AI Technical Summary
[0005]本发明提供了一种电解铜石墨烯复合箔及其制备方法,可以解决现有技术中石墨烯分散不均、界面结合弱的问题
(1)通过原位共沉积技术,实现石墨烯在铜基体中的均匀分散,避免了石墨烯团聚问题;
Smart Images

Figure CN122879769A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of conductive material preparation technology, and in particular to an electrolytic copper-graphene composite foil and its preparation method. Background Technology
[0002] Conductive materials are indispensable for realizing printed electronics technology. Currently, silver paste is mainly used as a conductive material in the field of printed electronics technology, but the high price of silver (about 60-80 times that of copper) limits its large-scale application.
[0003] Copper, as a substitute for silver, offers excellent electrical conductivity (approximately 95% of silver's) and low cost. However, copper readily oxidizes in air, forming an insulating copper oxide layer that drastically reduces its conductivity. Furthermore, the sintering temperature of traditional copper paste typically exceeds 200°C, making it incompatible with flexible substrates with poor temperature resistance (such as PET and PEN, which have a temperature resistance of approximately 130-180°C).
[0004] Graphene is a two-dimensional carbon material with extremely high electrical and thermal conductivity and mechanical strength. Combining graphene with copper can significantly improve the overall performance of copper-based materials. However, existing methods for preparing graphene-copper composites, including powder metallurgy, chemical vapor deposition, and electroplating, suffer from the following problems: Powder metallurgy results in uneven graphene dispersion in the copper matrix, leading to agglomeration and requiring high-temperature sintering, resulting in high energy consumption; chemical vapor deposition uses expensive equipment, hindering large-scale production; and electroplating results in weak bonding between graphene and copper, high interfacial resistance, and unresolved oxidation issues. Summary of the Invention
[0005] This invention provides an electrolytic copper-graphene composite foil and its preparation method, which can solve the problems of uneven graphene dispersion and weak interfacial bonding in the prior art.
[0006] In a first aspect, embodiments of the present invention provide a method for preparing electrolytic copper-graphene composite foil, comprising: Graphene oxide is dispersed in an electroplating solution to obtain a mixed solution; The mixture was co-deposited in situ to form a copper-graphene oxide composite layer; The copper-graphene oxide composite layer was reduced in a reducing atmosphere to obtain an electrolytic copper-graphene composite foil. The electrolytic copper-graphene composite foil is cooled to form a nanocrystalline gradient layer at the interface between the copper layer and the graphene.
[0007] Furthermore, the graphene oxide has a lateral dimension of 300-1000 nm and has 1-5 layers; the concentration of graphene oxide in the mixture is 0.05-0.5 g / L.
[0008] Furthermore, the electroplating solution contains copper sulfate pentahydrate, sulfuric acid, chloride ions, and a surfactant; the concentration of the surfactant is 0.01-0.1 g / L; the surfactant includes one or a combination of two or more of hexadecyltrimethylammonium bromide, sodium dodecyl sulfate, or polyvinylpyrrolidone.
[0009] Furthermore, the reduction treatment temperature is 200~400°C, the reduction treatment time is 1~4h; the reducing atmosphere is a mixture of hydrogen and nitrogen, and the volume fraction of hydrogen is 5~20%.
[0010] Furthermore, the cooling process is water quenching or nitrogen quenching, and the cooling rate is greater than 50°C / s.
[0011] Furthermore, the current density of the in-situ co-deposition is 1-10 A / dm².
[0012] Furthermore, the preparation method of the electrolytic copper graphene composite foil also includes: immersing the electrolytic copper graphene composite foil in a solution containing benzimidazole or thiourea for antioxidant treatment to form a self-assembled molecular protective layer.
[0013] Furthermore, the electroplating solution also includes a sulfur dopant, which includes one of thiourea, sodium thiosulfate, and cysteine, and the concentration of the dopant in the mixture is 0.001-0.01 g / L.
[0014] Secondly, embodiments of the present invention provide an electrolytic copper-graphene composite foil, wherein the electrolytic copper-graphene composite foil is prepared by any of the above-described methods for preparing electrolytic copper-graphene composite foil; the mass fraction of graphene in the electrolytic copper-graphene composite foil is 0.1-2%, and the thickness is 4-35 μm; the volume resistivity of the electrolytic copper-graphene composite foil is 1.5-2.0 μΩ·cm, and the tensile strength is 300-450 MPa.
[0015] Furthermore, the electrolytic copper-graphene composite foil includes an interface nanocrystalline gradient layer with a thickness of 20-100 nm, located at the interface region between the copper layer and the graphene.
[0016] Furthermore, the electrolytic copper graphene composite foil is used in flexible printed circuit substrates, electromagnetic shielding films, heat dissipation films, or 5G millimeter-wave antenna substrates.
[0017] The beneficial effects of this invention are: (1) The graphene is uniformly dispersed in the copper matrix by in-situ co-deposition technology, thus avoiding the problem of graphene agglomeration; (2) The introduction of sulfur dopant forms Cu-S chemical bonds at the interface between copper and graphene, which significantly enhances the interfacial bonding force and reduces the interfacial resistance. (3) Excellent antioxidant properties: The electrolytic copper-graphene composite foil prepared by the electrolytic copper-graphene composite foil preparation method has a volume resistivity change rate of less than 10% after being placed in air for 60 days; (4) Rapid cooling of the electrolytic copper-graphene composite foil after reduction treatment can form a nanocrystalline gradient layer at the interface between the copper layer and graphene, effectively alleviating thermal mismatch and solving the problem of mismatch between the thermal expansion coefficients of graphene and copper. Attached Figure Description
[0018] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on the structures shown in these drawings without creative effort.
[0019] Figure 1 This is a schematic diagram illustrating the preparation method of the electrolytic copper-graphene composite foil provided in an embodiment of the present invention.
[0020] Figure 2 This is a schematic diagram of an in-situ co-deposition apparatus provided in an embodiment of the present invention.
[0021] Figure 3 This is a schematic diagram of an electrolytic copper-graphene composite foil provided in an embodiment of the present invention.
[0022] Figure 4 This is a comparison chart showing the effect of anti-oxidation provided in the embodiments of the present invention with that of existing anti-oxidation methods.
[0023] Figure 5 This is a performance comparison chart of the electrolytic copper-graphene composite foil prepared by the method described in this paper and existing electrolytic copper-graphene composite foils.
[0024] Component labels in the diagram: 100-Electrolytic copper-graphene composite foil; 1-Copper; 2-Graphene layer.
[0025] The realization of the objective, functional features and advantages of the present invention will be further explained in conjunction with the embodiments and with reference to the accompanying drawings. Detailed Implementation
[0026] The following embodiments are provided to better understand the present invention and are not limited to the preferred embodiments described. They do not constitute a limitation on the content and scope of protection of the present invention. Any product that is the same as or similar to the present invention, derived by any person under the guidance of the present invention or by combining the features of the present invention with other prior art, falls within the protection scope of the present invention.
[0027] Unless otherwise stated or in case of contradiction, the terms or phrases used herein shall have the following meanings: In this invention, the selection range involving "and / or" includes any one of two or more related listed items, as well as any and all combinations of the related listed items. For example, "A and / or B" includes three parallel schemes: A, B, and A+B.
[0028] In this invention, the terms "multiple" or "multiple types" are used unless otherwise specified, referring to a quantity greater than or equal to 2. For example, "one or more" means one or more types.
[0029] In this invention, terms such as "further," "even more," and "particularly" are used for descriptive purposes to indicate differences in content, but should not be construed as limiting the scope of protection of this invention.
[0030] In this invention, the terms "optionally," "optionally," and "optional" refer to options that are optional, meaning they are selected from either "with" or "without." If multiple "optional" options appear in a technical solution, unless otherwise specified and there are no contradictions or mutual constraints, each "optional" option is independent.
[0031] In this invention, the terms "first aspect," "second aspect," "third aspect," and "fourth aspect," etc., are used for descriptive purposes only and should not be construed as indicating or implying relative importance or quantity, nor should they be construed as implicitly indicating the importance or quantity of the indicated technical features. Moreover, "first," "second," "third," and "fourth," etc., serve only as a non-exhaustive enumeration and should be understood not to constitute a closed limitation on quantity.
[0032] In this invention, the technical features described in an open-ended manner include both closed-ended technical solutions composed of the listed features and open-ended technical solutions that include the listed features.
[0033] For experiments not specifically described in the examples, the procedures or conditions should be followed according to the conventional experimental procedures described in the literature in this field. Reagents or instruments whose manufacturers are not specified are all commercially available conventional reagent products.
[0034] Example 1 Please refer to Figure 1 This invention provides a method for preparing electrolytic copper-graphene composite foil, comprising the following steps.
[0035] S10, dispersing graphene oxide in an electroplating solution to obtain a mixed solution.
[0036] In this embodiment, the concentration of graphene oxide is 0.05-0.5 g / L. The electroplating solution contains copper sulfate, sulfuric acid (H2SO4), and chloride ions (Cl). - Copper sulfate, and surfactants. Copper sulfate pentahydrate (CuSO4·5H2O) is preferred. Chloride ions (Cl... - The surfactant is provided by sodium chloride (NaCl). The concentration of the surfactant is 0.01-0.1 g / L, and the surfactant includes one or a combination of two or more of hexadecyltrimethylammonium bromide (CTAB), sodium dodecyl sulfate (SDS), and polyvinylpyrrolidone (PVP). In this embodiment, sodium dodecyl sulfate (SDS) is selected as the surfactant, and sodium chloride is selected as the chloride ion.
[0037] The electroplating solution also includes a sulfur dopant, which includes one of thiourea, sodium thiosulfate, and cysteine, and the concentration of the dopant in the mixture is 0.001-0.01 g / L.
[0038] In this embodiment, the components and concentrations of the electroplating solution are as follows: Copper sulfate pentahydrate: 200g / L Sulfuric acid: 50g / L Sodium chloride: 60 mg / L Sodium dodecyl sulfate: 0.05 g / L Thiourea: 0.005 g / L Graphene oxide was ultrasonically dispersed in deionized water, and an electroplating solution was added and stirred until homogeneous to obtain a mixture. The concentration of graphene oxide in the mixture was 0.05 g / L-0.5 g / L. In this embodiment, the graphene oxide used had a lateral dimension of 300 nm-1000 nm, 1-5 layers, and a specific concentration of 0.2 g / L in the mixture. The sulfur dopant synergistically interacts with the graphene oxide to form Cu-S chemical bonds in the copper matrix, enhancing the interfacial bonding between graphene and copper.
[0039] In this embodiment, the mixture also includes other additives, such as leveling agents and brighteners. Brighteners are used to refine the coating grains and improve the coating brightness. Leveling agents preferentially adsorb onto microscopic protrusions in the coating, inhibiting copper deposition at these protrusions and smoothing the coating's microstructure. Wetting agents are used to reduce the surface tension of the plating solution and decrease pinhole defects in the coating. The brightener concentration is 5-50 mg / L, and the leveling agent concentration is 1-200 mg / L.
[0040] S20, the mixture is co-deposited in situ to form a copper-graphene oxide composite layer.
[0041] The in-situ co-deposition current density ranges from 1 A / dm² to 10 A / dm². For example... Figure 2 As shown, in this embodiment, a titanium-coated iridium anode and a stainless steel cathode (with a mirror-polished surface) are used. The current density is 5A / dm², the temperature of the mixed solution is 25°C, and the in-situ co-deposition time is 30 minutes. Copper ions and graphene oxide are co-deposited on the cathode surface to obtain a copper-graphene oxide composite layer with a thickness of about 12μm.
[0042] S30, the copper-graphene oxide composite layer is reduced in a reducing atmosphere to obtain an electrolytic copper-graphene composite foil.
[0043] The reduction treatment temperature is 200°C to 400°C, and the reduction treatment time is 1 hour to 4 hours. The reducing atmosphere is a mixture of hydrogen and nitrogen, with the hydrogen volume fraction being 5% to 20%.
[0044] In this embodiment, the copper-graphene oxide composite layer was heat-treated at 300°C for 2 hours in a mixed atmosphere of hydrogen and nitrogen in a ratio of 1:9 to obtain an electrolytic copper-graphene composite foil.
[0045] S40, the electrolytic copper-graphene composite foil is cooled to form a nanocrystalline gradient layer at the interface between the copper layer and the graphene.
[0046] The cooling process involves water quenching or nitrogen quenching at a rate greater than 50°C / s. Specifically, after the reduction treatment described above, the electrolytic copper-graphene composite foil undergoes rapid cooling, causing the copper-graphene interface to drop from the heat treatment temperature to below 100°C within 2 seconds. This allows a nanocrystalline gradient layer to form at the copper-graphene interface, mitigating the mismatch in thermal expansion coefficients. At this point, the bonding strength between the copper-graphene interface increases by approximately 30%.
[0047] S50, the electrolytic copper graphene composite foil is immersed in a solution containing benzimidazole or thiourea for antioxidant treatment to form a self-assembled molecular protective layer.
[0048] Specifically, the electrolytic copper graphene composite foil was immersed in a 0.5 g / L benzimidazole ethanol solution and treated at room temperature for 30 minutes. The electrolytic copper graphene composite foil was then removed and dried, thereby achieving the antioxidant treatment of the electrolytic copper graphene composite foil and giving it excellent antioxidant properties.
[0049] The electrolytic copper-graphene composite foil obtained in step S50 was subjected to performance testing. The test results showed that the graphene content was 0.8 wt%, the volume resistivity was 1.72 μΩ·cm, which was comparable to 1.68 μΩ·cm of pure copper foil, maintaining excellent conductivity; the tensile strength was 380 MPa, which was significantly improved compared to 280 MPa of pure copper foil; and the resistivity change rate of the electrolytic copper-graphene composite foil after being placed in air for 60 days was 8.5%.
[0050] Comparative Example 1 Electrolytic copper-graphene composite foil was prepared according to the preparation method of Example 1, but sulfur dopant was not added to the electroplating solution, and the other steps were the same as in Example 1.
[0051] The performance of the obtained electrolytic copper graphene composite foil was tested. The test results showed that the volume resistivity of the electrolytic copper graphene composite foil was 1.85 μΩ·cm; the volume resistivity change rate of the electrolytic copper graphene composite foil after being placed in air for 60 days was 22%.
[0052] Table 1 Comparison between Comparative Example 1 and Example 1 As can be seen from the data in Table 1, compared with the test results of Example 1, the volume resistivity and volume resistivity change rate of the electrolytic copper graphene composite foil of Comparative Example 1 are significantly worse than those of Example 1. This indicates that sulfur dopant plays an important role in the interfacial bonding and antioxidant properties of the electrolytic copper graphene composite foil.
[0053] This invention also provides an electrolytic copper-graphene composite foil prepared by the method described in Example 1 above. The electrolytic copper-graphene composite foil contains 0.1%-2% graphene by mass and has a thickness of 4μm-35μm. The electrolytic copper-graphene composite foil has a volume resistivity of 1.5μΩ·cm-2.0μΩ·cm and a tensile strength of 300MPa-450MPa. After being placed in air for 60 days, the volume resistivity of the electrolytic copper-graphene composite foil changes by less than 10%.
[0054] Furthermore, the electrolytic copper-graphene composite foil includes an interfacial nanocrystalline gradient layer with a thickness of 20nm-100nm, located at the interface between the copper layer and graphene. This interfacial nanocrystalline gradient layer is formed by rapid cooling, with the grain size gradually transitioning from 50nm on the copper side to 5nm on the graphene side. This interfacial nanocrystalline gradient layer ensures that the volume resistivity of the electrolytic copper-graphene composite foil changes by less than 5% during temperature cycling tests (test environment: -40°C to +85°C, 1000 cycles).
[0055] This invention also provides the application of the electrolytic copper-graphene composite foil prepared by the above-described method in flexible printed circuit substrates, electromagnetic shielding films, heat dissipation films, or 5G millimeter-wave antenna substrates. The following description uses flexible printed circuit substrates and electromagnetic shielding films as examples.
[0056] Flexible printed circuit substrate: A flexible printed circuit is fabricated using the aforementioned electrolytic copper-graphene composite foil as a substrate and forming circuit patterns through photolithography or laser direct writing processes. Its linewidth reaches 20μm-100μm. The flexible printed circuit can be repeatedly bent with a bending radius of 5mm and a bending cycle of more than 10,000 times without affecting its conductivity.
[0057] Electromagnetic shielding film: An electromagnetic shielding film prepared from the electrolytic copper-graphene composite foil has a thickness of 10μm-50μm and a shielding effectiveness greater than 60dB in the 10MHz-10GHz frequency band. The shielding film can be attached to the inside of the electronic device housing to suppress electromagnetic interference. A protective coating with a thickness of 1μm-5μm can be coated on the surface of the shielding film to prevent oxidation and mechanical scratches. The protective coating is a UV-cured acrylate or polyurethane.
[0058] Please refer to Figure 3 and Figure 4 , Figure 3 The diagram shows a comparison of the anti-oxidation effects of electrolytic copper-graphene composite foil prepared using the method provided by this invention with existing electrolytic copper-graphene composite foil. Figure 4 This is a performance comparison chart of the electrolytic copper-graphene composite foil prepared by the method provided in this invention and existing electrolytic copper-graphene composite foils.
[0059] The beneficial effects of this invention are: (1) The graphene is uniformly dispersed in the copper matrix by in-situ co-deposition technology, thus avoiding the problem of graphene agglomeration; (2) The introduction of sulfur dopant forms Cu-S chemical bonds at the interface between copper and graphene, which significantly enhances the interfacial bonding force and reduces the interfacial resistance. (3) Excellent antioxidant properties: The electrolytic copper-graphene composite foil prepared by the electrolytic copper-graphene composite foil preparation method has a volume resistivity change rate of less than 10% after being placed in air for 60 days; (4) Rapid cooling of the electrolytic copper-graphene composite foil after reduction treatment can form a nanocrystalline gradient layer at the interface between the copper layer and graphene, effectively alleviating thermal mismatch and solving the problem of mismatch between the thermal expansion coefficients of graphene and copper.
[0060] Obviously, those skilled in the art can make various modifications and variations to this invention without departing from its spirit and scope. Therefore, if these modifications and variations fall within the scope of the claims of this invention and their equivalents, this invention also intends to include these modifications and variations.
[0061] The above-listed embodiments are merely preferred embodiments of the present invention and should not be construed as limiting the scope of the present invention. Therefore, any equivalent variations made in accordance with the claims of the present invention are still within the scope of the present invention.
Claims
1. A method for preparing an electrolytic copper-graphene composite foil, characterized in that, The preparation method of the electrolytic copper-graphene composite foil includes: Graphene oxide is dispersed in an electroplating solution to obtain a mixed solution; The mixture was co-deposited in situ to form a copper-graphene oxide composite layer; The copper-graphene oxide composite layer was reduced in a reducing atmosphere to obtain an electrolytic copper-graphene composite foil. The electrolytic copper-graphene composite foil is cooled to form a nanocrystalline gradient layer at the interface between the copper layer and the graphene.
2. The method for preparing electrolytic copper-graphene composite foil as described in claim 1, characterized in that, The graphene oxide has a lateral dimension of 300-1000 nm and 1-5 layers; the concentration of graphene oxide in the mixture is 0.05-0.5 g / L.
3. The method for preparing electrolytic copper-graphene composite foil as described in claim 1, characterized in that, The electroplating solution contains copper sulfate pentahydrate, sulfuric acid, chloride ions, and a surfactant; the concentration of the surfactant is 0.01-0.1 g / L; the surfactant includes one or a combination of two or more of hexadecyltrimethylammonium bromide, sodium dodecyl sulfate, or polyvinylpyrrolidone.
4. The method for preparing electrolytic copper-graphene composite foil as described in claim 1, characterized in that, The reduction treatment temperature is 200~400°C, and the reduction treatment time is 1~4h; the reducing atmosphere is a mixture of hydrogen and nitrogen, and the volume fraction of hydrogen is 5~20%.
5. The method for preparing electrolytic copper-graphene composite foil as described in claim 1, characterized in that, The cooling process is water quenching or nitrogen quenching, and the cooling rate is greater than 50°C / s.
6. The method for preparing electrolytic copper-graphene composite foil as described in claim 1, characterized in that, The current density of the in-situ co-deposition is 1-10 A / dm².
7. The method for preparing electrolytic copper-graphene composite foil as described in claim 1, characterized in that, The preparation method of the electrolytic copper graphene composite foil further includes: immersing the electrolytic copper graphene composite foil in a solution containing benzimidazole or thiourea for antioxidant treatment to form a self-assembled molecular protective layer.
8. The method for preparing electrolytic copper-graphene composite foil as described in claim 1, characterized in that, The electroplating solution also includes a sulfur dopant, which includes one of thiourea, sodium thiosulfate, and cysteine, and the concentration of the dopant in the mixture is 0.001-0.01 g / L.
9. An electrolytic copper-graphene composite foil, characterized in that, The electrolytic copper graphene composite foil is prepared by the preparation method of the electrolytic copper graphene composite foil according to any one of claims 1-8; the mass fraction of graphene in the electrolytic copper graphene composite foil is 0.1-2%, and the thickness is 4-35 μm; the volume resistivity of the electrolytic copper graphene composite foil is 1.5-2.0 μΩ·cm, and the tensile strength is 300-450 MPa.
10. The electrolytic copper-graphene composite foil as described in claim 9, characterized in that, The electrolytic copper-graphene composite foil includes an interface nanocrystalline gradient layer with a thickness of 20-100 nm, located at the interface region between the copper layer and the graphene.
11. The electrolytic copper-graphene composite foil as described in claim 9, characterized in that, The electrolytic copper graphene composite foil is used in flexible printed circuit substrates, electromagnetic shielding films, heat dissipation films, or 5G millimeter-wave antenna substrates.